Cardiac findings and events observed in an open-label clinical trial of tafamidis in patients with non-Val30Met and non-Val122Ile hereditary transthyretin amyloidosis - Damy, Thibaud; Kristen, Arnt (Journal of cardiovascular translational research, 2015)
A phase 2, open-label study in 21 patients with non-Val30Met and non-Val122Ile hereditary transthyretin amyloidosis showed that tafamidis (20 mg daily for 12 months) stabilized these transthyretin variants. We assessed cardiac amyloid infiltration and cardiac abnormalities in this same study population. At baseline, median age was 64.3 years, 11 patients were in NYHA class II, 13 had conduction abnormalities, 14 N-terminal pro-hormone brain natriuretic peptide concentrations >300 pg/ml, and 17 interventricular septal thickness >12 mm. Mean (SD) left ventricular ejection fraction was 60.3 % (9.96). Patients with normal heart rate variability increased from 4/19 at baseline to 8/19 at month 12 (p < 0.05). Cardiac biomarkers remained stable. Although four patients had increases in interventricular septal thickness ≥2 mm, the remainder had stable septal wall thickness. There were no clinically relevant changes in mean echocardiographic/electrocardiographic variables and no safety concerns.